Discourse-level comprehension engages medial frontal Theory of Mind brain regions even for expository texts. Issue 6 (2nd July 2020) - Jacoby, Nir; Fedorenko, Evelina
ABSTRACT: In addition to understanding individual word meanings and processing the syntactic and semantic dependencies among those words within a sentence, language comprehension often requires constructing a higher-order discourse structure based on the relationships among clauses and sentences in the extended context. Prior fMRI studies of discourse-level comprehension have reported greater activation for texts than unconnected sentences in what-appear-to-be regions of the Theory of Mind (ToM) network. However, those studies have generally used narratives rich in mental state content, thus confounding coherence and content. We report an fMRI experiment where ToM regions were defined functionally in each participant, and their responses were examined to texts vs. sentence lists. Critically, we used expository texts to minimise mental state content. Medial frontal but not posterior ToM regions exhibited small but reliable increases in their responses to texts relative to unconnected sentences, suggesting a role for these regions in discourse comprehension independent of content.